Fuzzy engineering - Kosko, Bart (Prentice Hall, 1997)
This book introduces an important new framework for fuzzy systems and applies it to several engineering applications. Broad in scope, this is a must-read for anyone doing research or applications. KEY TOPICS: " Applications reach far beyond the usual fuzzy applications to control. Each chapter starting with a tutorial overview, presents new research results, and ends with detailed problems. Specific discussion is dedicated to fuzzy function approximation, fuzzy chaos and control, fuzzy signal processing, fuzzy communication, fuzzy hardware, computing in fuzzy cubes, and feedback in fuzzy cubes.